Comprehension of readmission after laparoscopy assisted distal gastrectomy: what are the causes? - Kim, Min-Chan (The Korean Surgical Society, 2014)
PURPOSE: The aim of this study is to evaluate long-term outcomes regarding readmission for laparoscopy-assisted distal subtotal gastrectomy (LADG) compared to conventional open distal subtotal gastrectomy (CODG) for early gastric cancer (EGC). METHODS: Between January 2003 and December 2006, 223 and 106 patients underwent LADG and CODG, respectively, for EGC by one surgeon. The clinicopathologic characteristics, postoperative outcomes, postoperative complications, overall 5-year survival, recurrence, and readmission were retrospectively compared between the two groups. RESULTS: Multiple readmission rate in LADG was significantly less than that in CODG (0.4% vs. 3.8%, P = 0.039), although the readmission rate, reoperation rate after discharge, and mean readmission days were not significantly different between the two groups. Readmission rates of the LADG and CODG groups were 12.6% and 14.2%, respectively. First flatus time and postoperative hospital stay was significantly shorter in the LADG group. However, there was no significant difference in the complication rates between the two groups. Overall 5-year survival rates of the LADG and CODG group were 100% and 99.1% (P = 0.038), respectively. CONCLUSION: Compared to the CODG group, the LADG group has several advantages in surgical short-term outcome and some benefit in terms of readmission in surgical long-term outcome for patients with EGC, even though the oncologic outcome of LADG is similar to that of CODG over 5 years.